2003
DOI: 10.4018/jdet.2003010101
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Distance Education Challenges and Technologies

Abstract: Distance education, e-learning, and virtual university are similar terms for a trend of modern education. It is an integration of information technologies, computer hardware systems, and communication tools to support educational professionals in remote teaching. This chapter presents an overview of distance education from the perspective of policy, people, and technology. A number of questions frequently asked in distance learning panel discussions are presented, with the suggested answers from the authors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…Several researchers (Griffiths, 2016 ; Ko et al, 2022 ; Lalitha & Sreeja, 2020 ; Shih et al, 2003 ; Utomo et al, 2020 ) have identified the methodologies and learning strategies adapted to conduct distance learning as asynchronous or synchronous learning. In the virtual synchronous learning method, an instructor is available in real time for assistance, whereas the asynchronous learning method consists of recorded or deferred lessons.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Several researchers (Griffiths, 2016 ; Ko et al, 2022 ; Lalitha & Sreeja, 2020 ; Shih et al, 2003 ; Utomo et al, 2020 ) have identified the methodologies and learning strategies adapted to conduct distance learning as asynchronous or synchronous learning. In the virtual synchronous learning method, an instructor is available in real time for assistance, whereas the asynchronous learning method consists of recorded or deferred lessons.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several authors by Lalitha & Sreeja, ( 2020 ) Zorrilla et al, ( 2010 ) also discussed a blended or hybrid learning strategy in which a combination of both synchronous and asynchronous methods is adopted. Furthermore, Lalitha and Sreeja described a self-learning strategy, in which learners adapt to the self-learning method and the open distance learning method proposed (Shih et al, 2003 ), where the learners learn in a self-paced environment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This importance is due in part to the role that management education has in facilitating strategic change within and across industries (Walton, 1999). Furthermore, management education additional alternatives to traditional face-toface classroom education (Karns and Pharr, 2001;Shih et al, 2003). However, whilst online learning is becoming increasingly popular, research surrounding its effectiveness is surprisingly underdeveloped.…”
Section: Introductionmentioning
confidence: 99%